2022
DOI: 10.1155/2022/5912396
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects and Metabolic Spectrum of Traditional Chinese Medicine Hengqing II Prescription on Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) seriously damages elders’ social and daily abilities around the world. Traditional Chinese medicine (TCM), a rich drug resource bank, could help research AD. In order to explore the role of TCM in AD treatment, 86 AD patients were recruited from the hospital, then treated with Hengqing II prescription and donepezil hydrochloride. The cognitive and serum lipid levels were investigated before and after treatment. The patient’s urine was collected after three months of treatment. Metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
0
0
Order By: Relevance
“…As shown in Figure 6D , 15 metabolic pathways were collectively enriched by differential metabolites. Studies have found that metabolic pathways related to AD include Arginine biosynthesis, 28 Taurine and hypotaurine metabolism, 29 PPAR signaling pathway, 30 Glycerophospholipid metabolism, 31 and Linoleic acid metabolism. Among them, the PPAR signaling pathway is closely related to neuroinflammation.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 6D , 15 metabolic pathways were collectively enriched by differential metabolites. Studies have found that metabolic pathways related to AD include Arginine biosynthesis, 28 Taurine and hypotaurine metabolism, 29 PPAR signaling pathway, 30 Glycerophospholipid metabolism, 31 and Linoleic acid metabolism. Among them, the PPAR signaling pathway is closely related to neuroinflammation.…”
Section: Resultsmentioning
confidence: 99%